A Study on the Reaction between Phenacyl Bromide and Certain Tertiary Amines In Acetone: Effect of Addition of Water and Phenol(s) - Nallu, M. (Asian Journal of Chemistry, 2012)
Rate constants for the reaction between phenacyl bromide and certain tertiary amines have been determined conductometrically using Guggehiem’s method under equimolar concentrations at 30ºC. The rate is correlated with steric effects of bases(s). Effects of addition of water and phenol(s) on the rate of the reaction between phenacyl bromide and triethylamide are discussed. The critical region in aq. acetone mixed solvents for this reaction is reported Phenol(s) with pka> 7.15 does not affect the rate of quaternization in all concentrations of waterv in acetone, whereas p-nitrophenol retards the rate just by the addition of water.